Phenylpropanoids from Brachybotrys paridiformis maxim. Ex oliv. And their anti-HBV activities (II). (November 2022) - Wu, Si-Tong; Li, Fei; Wang, Yi-Xiao; Yu, Bai-Hong; Ma, Chun-Liu; Qiu, He-Qin; Wang, Guang-Shu
Abstract: Five undescribed phenylpropanoids, one undescribed phenolic glucoside, and sixteen known compounds were isolated from Brachybotrys paridiformis Maxim. Ex Oliv. The undescribed compounds were named brachoside B–C, brach acid A–B, brachnan A, and brachin D, respectively. Additionally, the anti-hepatitis B virus activities of all isolated compounds were studied. Among them, brachnan A, brach acid A, globoidnan A, 3-carboxy-6, 7-dihydroxy-1-(3′, 4′-dihydroxy-phenyl)-naphthalene, and 3, 4-dihydroxybenzaldehyde showed significant anti-hepatitis B virus activities. Graphical abstract: Phenylpropanoids were isolated from Brachybotrys paridiformis, and their anti-HBV activities were studied. The picture of B. Paridiformis was obtained from the Plant Photo Bank of China. Image 1 Highlights: This is a study on the herb Brachybotrys paridiformis. Five undescribed phenylpropanoids and one phenolic glucoside are obtained. The main compounds isolated are phenylpropanoids and their derivatives. The anti-HBV activities of the isolated compounds are reported.